2007
DOI: 10.1177/0306624x07301643
|View full text |Cite
|
Sign up to set email alerts
|

Using the Violence Risk Appraisal Guide (VRAG) to Predict In-Prison Aggressive Behavior in a Swiss Offender Population

Abstract: The present study is a first-time evaluation of the Violence Risk Appraisal Guide's (VRAG) predictive quality for institutional violence in a German-speaking country. The VRAG was assessed for 106 violent and sexual offenders based on their files. Violent infractions during imprisonment were evaluated using the files of the state penitentiary. Results show in accordance with previous studies only a moderate effect between VRAG scores and institutional misconduct. However, these findings were only significant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
(32 reference statements)
1
6
1
2
Order By: Relevance
“…Our results for the prevalence of misconduct are similar to those reported by several other studies of physically violent misconduct (Lahm, ; Wooldredge & Steiner, ), but the rates we found were much lower than those reported by previous studies carried out in Switzerland (Endrass, Rossegger, Frischknecht, et al, ; Endrass, Rossegger, Urbaniok, et al, ; Pont et al, ). This may be due to differences in situational factors, which have been shown to impact rates of physically violent misconduct by prisoners (Schenk & Fremouw, ; Welsh, Bader, & Evans, ) and/or to differences in methodology.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results for the prevalence of misconduct are similar to those reported by several other studies of physically violent misconduct (Lahm, ; Wooldredge & Steiner, ), but the rates we found were much lower than those reported by previous studies carried out in Switzerland (Endrass, Rossegger, Frischknecht, et al, ; Endrass, Rossegger, Urbaniok, et al, ; Pont et al, ). This may be due to differences in situational factors, which have been shown to impact rates of physically violent misconduct by prisoners (Schenk & Fremouw, ; Welsh, Bader, & Evans, ) and/or to differences in methodology.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in Spain (Arbach‐Lucioni, Martinez‐García, & Andrés‐Pueyo, ) and Taiwan (Kuo, Cuvelier, & Huang, ) reported similar US average rates of prisoner‐to‐prisoner physical violence (8%), but the Taiwan study showed a much higher rate of prisoner‐to‐prisoner psychological violence (21%). According to two studies based on records from a single Swiss prison, 28% of prisoners said they had been victims of prisoner‐to‐prisoner physical violence, 26% had been subject to verbal violence, and 15% had taken illegal drugs during their incarceration (Endrass, Rossegger, Frischknecht, Noll, & Urbaniok, ; Endrass, Rossegger, Urbaniok, Laubacher, & Vetter, ). More recently, a 1‐year survey of a Swiss pre‐sentencing prison found that 30% of inmates had reported being victims of prisoner‐to‐prisoner physical violence (Pont et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the majority of the extracted investigations found a significant association with an outcome, the included studies are commonly interpreted as proof of the robustness of the VRAG, SORAG, and Static‐99 (e.g., Hastings, Krishnan, Tangney, & Stuewig, ; Kröner, Stadtland, Eidt, & Nedopil, ) though the purported replication investigations differed with respect to the follow‐up period (Quinsey, Book, & Skilling, ; Rettenberger, Matthes, Boer, & Eher, ), the composition of the study sample (Harris, Rice, & Cormier, ; Hastings et al, ; Snowden, Gray, & Taylor, ), and the definition of the outcome criterion (Endrass, Rossegger, Frischknecht, Noll, & Urbaniok, ; Harris & Rice, ; Harris et al, ; Hastings et al, ; Kroner & Mills, ; Lindsay et al, ; Loza, Villeneuve, & Loza‐Fanous, ; Storey, Watt, Jackson, & Hart, ). Deviations from the methodology used in the development study were interpreted as corroboration of model robustness (Harris & Rice, ; Harris et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Zwei aktuelle Untersuchungen aus der Schweiz konnten die Tendenz der Ergebnisse jedoch replizieren: Bei Gewalt-und Sexualstraftätern im Zürcher Strafvollzug (Strafanstalt Pöschwies) erwiesen sich die Psychopathie-Gheckliste und der VRAG als nicht oder nur sehr gering prädiktiv für physische Gewalt [5,19]. …”
Section: Prognoseinstrumente Und Gewalt Im Strafvollzugunclassified